2007
DOI: 10.1128/jb.00946-07
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of the Rhodobacter sphaeroides 2.4.1 Photosynthetic Membrane: Identification of New Proteins

Abstract: The Rhodobacter sphaeroides intracytoplasmic membrane (ICM) is an inducible membrane that is dedicated to the major events of bacterial photosynthesis, including harvesting light energy, separating primary charges, and transporting electrons. In this study, multichromatographic methods coupled with Fourier transform ion cyclotron resonance mass spectrometry, combined with subcellular fractionation, was used to test the hypothesis that the photosynthetic membrane of R. sphaeroides 2.4.1 contains a significant n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
40
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 33 publications
12
40
1
Order By: Relevance
“…Relative quantitative comparisons between proteomes associated with each cell culture were based upon two "label-free" proteomic approaches: (i) the total number of peptides detected for a protein ("mass tag") (77), and (ii) the sum of abundances of peptides (determined by integrating the areas under each peak of the LC-FTICR-MS spectra for a detected peptide) for a protein ("abundance") (8) in four replicates emanating from WT and mutant PrrA2 cultures and expressed as either a "mass tag" or an "abundance" ratio between WT and PrrA2 cells (1). By comparing these abundance metrics for each specific protein only to itself in WT cells, as opposed to PrrA2 cells, we eliminated the bias inherent to the proportionality of protein mass to its abundance in terms of the number of specific peptides detected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative quantitative comparisons between proteomes associated with each cell culture were based upon two "label-free" proteomic approaches: (i) the total number of peptides detected for a protein ("mass tag") (77), and (ii) the sum of abundances of peptides (determined by integrating the areas under each peak of the LC-FTICR-MS spectra for a detected peptide) for a protein ("abundance") (8) in four replicates emanating from WT and mutant PrrA2 cultures and expressed as either a "mass tag" or an "abundance" ratio between WT and PrrA2 cells (1). By comparing these abundance metrics for each specific protein only to itself in WT cells, as opposed to PrrA2 cells, we eliminated the bias inherent to the proportionality of protein mass to its abundance in terms of the number of specific peptides detected.…”
Section: Methodsmentioning
confidence: 99%
“…For some proteins, discrepancies between both quantitative approaches were observed, which was not surprising because of the variability associated with "label-free" quantitative proteomic approaches in general (6). In light of this variability, both approaches were used for comparison with transcriptome measurements, as has been previously described (77) . FIG.…”
Section: Vol 190 2008mentioning
confidence: 99%
“…Extracts containing equal amounts of protein (as determined with a bicinchoninic acid assay kit from Pierce used as recommended by the manufacturer) were used to determine the spectral data with a UV2450 spectrophotometer (Shimadzu Corp., Columbia, MD). The B800-850 and B875 complex levels were determined using the data collected, as reported previously (52).…”
Section: Methodsmentioning
confidence: 99%
“…The R. sphaeroides strains and plasmid used in this study are shown in Table 1. R. sphaeroides strains were grown aerobically in Sistrom's minimal medium A containing succinate with a gas mixture containing 30% O 2 , 69% N 2 , and 1% CO 2 and anaerobically in the dark in Sistrom's minimal medium A supplemented with yeast extract (0.1%, wt/vol) and DMSO (0.5%, vol/vol) with a gas mixture containing 95% N 2 and 5% CO 2 (45,52). Aerobic and anaerobic cells were harvested at optical densities at 600 nm of 0.2 Ïź 0.05 and 0.45 Ïź 0.05, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Rhodobacter sphaeroides 2.4.1 is a purple nonsulfur bacterium which belongs to the Alpha-3-proteobacteria, whose members exhibit diversity in both their morphological and metabolic characteristics. With the availability of its genomic DNA sequence (http://www.rhodobacter.org) and the R. sphaeroides GeneChip (67), transcriptome and proteome analyses have been performed to investigate global cellular expression profiles in response to changes in growth conditions, as well as to the presence of specific mutations (1,5,6,8,9,29,61,72,89).…”
mentioning
confidence: 99%